The Rehoboth Rebellion - Pearson, Patrick (My University, 1978)
At dawn on the 5th of April 1925, a force of 621 men comprising citizen force troops and police surrounded the town of Rehoboth in South West Africa. Their object was to secure the arrest of three men who had failed to respond to summonses issued under the stock branding proclamation. Seven days previously a large group of supporters had prevented three local policemen from entering the building where the men were staying. In response to this act of defiance, the Administrator had mobilized the citizen force in nine districts and declared martial law in Rehoboth.
African Studies Seminar series. Paper presented 1978
Keywords: Rehoboth (Namibia). History; Namibia. History, 1915-1946